THE SYNCRETISM OF SCIENTIFIC APPROACHES AND EDUCATIONALPRACTICE IN THE FOCUS OF EFFECTIVENESS AND SUSTAINABILITYTHROUGH EDUCATION - Kaneva, Ophelia (E-Journal VFU, 2024)
This article shares thoughts about the possibilities of decentralization and partnership in education with forward-thinking on the value of engaged stakeholders, referencing global practices.Based on this, it provokes the opportunity for an analysis of future policies regarding education, societal needs, transdisciplinary creativity, and practical contributions.The aim of the exposition is to impact thinking about education and decentralization, recognizing them as agents of change in their interaction, influencing the present adequately, and thus shaping a positive future on political, societal, economic, and academic levels.
Keywords: effectiveness in education; public-private partnership; decentralization; management